Building Collective Leadership for Culture Change : Stories of Relational Organizing on Campus and Beyond - Avila, Maria, 1955-; Vieira, Philip A.; Chai, Kathleen Tornow; Knoerr, Alan P., 1957-; Perez, Joanna B.; Rivera, Aixle Aman (Book collections on Project MUSE., 2023)
"This book is about how, by using community organizing, research in action, and narrative inquiry, five research projects were able to create more collaborative and participatory cultures in their academic institutions and in other non-academic settings."--